Effectiveness and safety of Adalimumab in psoriasis and its influence on gut microbiome. (January 2022) - Zhao, Lihong; Zhang, Xinyue; Zhu, Longfei; Geng, Songmei; Guo, Kun
Abstract: Psoriasis is an inflammatory immune-mediated skin disease that significantly impacts physical and psychological well-being. Adalimumab (ADA), a tumor necrosis factor (TNF)-α antagonist, is used to treat psoriasis. This study was performed to assess the efficacy and safety of ADA, identify the fecal microbial composition of psoriasis patients, and explore the effect of ADA on the gut bacteria in psoriasis. Clinical characteristics of the 13 psoriasis patients before (BT) and after ADA treatment (AT) were collected. And total 39 fecal samples from 13 psoriasis patients (BT and AT) and 13 healthy controls were sequenced by 16S rRNA and analyzed by informatics methods. After three months' ADA treatment, physician global assessment (PGA), psoriasis area and severity index (PASI), dermatology life quality index (DLQI), state-trait anxiety inventory (STAI), and itch numeric rating scale (NRS) scores all decreased, and there were no severe adverse effects. Besides, the microbiota of the psoriasis group differed from that of the healthy group, but no microbial diversity and composition alteration were observed between psoriasis patients BT and AT. We suggested that the gut microbiome may change more slowly than skin lesions. Long-term follow-up of patients treated with ADA and further study of psoriasis based on microbiota may provide more evidence for the treatment of psoriasis. Highlights: We analyzed the efficacy and safety of Adalimumab in the treatment of psoriasis patients. Our study demonstrated the differences in the microbiome composition between psoriasis patients and healthy controls. We compared changes in the pre-treatment and post-treatment intestinal microbiome composition in psoriasis patients with Adalimumab treatment.